Analysis of the aerodynamics by experimental testing of an elite wheelchair sprinter - Barbosa, T. M.; Forte, P.; Estrela, J. E.; Coelho, E. (Procedia Engineering, 2016)
The aim was to compare the resistive forces acting upon an European wheelchair medallist. The coast-down technique was selected to estimate the resistance in the upright position and racing positions with the neck in hyperextension and flexion, respectively. In the upright position, racing position with the neck in flexion and hyperextension the effective surface area was 0.1747, 0.1482 and 0.1456m2, respectively. The coefficient of rolling friction was 0.00119, 0.00489, 0.00618 and the power to overcome drag 26.62, 22.59, 22.19W for the same positions. As a conclusion, the resistance acting upon the sprinter is different according to his position on the chair. Slight changes in the head position over the race can affect by almost 2% the power output.